A revealed preference study of management journals’ direct influences - Tahai, Alireza; Meyer, Michael J. (Strategic Management Journal, 1999)
Our study develops and uses a new methodology for analyzing journal citations to recent publications to determine which management journals now have the greatest influence on the field of management. It analyzes the 23637 academic journal references cited in the 1275 articles published in 17 key management journals during 1993 and 1994, focusing on citations to references published up to the modal vintage of 4 years earlier. Most cited as a percentage of all these references was Strategic Management Journal (11%), followed by Academy of Management Journal, Journal of Applied Psychology, Organizational Behavior and Human Decision Processes, Academy of Management Review, Administrative Sciences Quarterly, and Journal of Management—accounting in total for 51 percent of all citations. Strategic Management Journal, whose subfield of strategic management has become a major concern of management in general, has developed as the predominant academic journal influencing the field of management. Our measures of journal influence provide information which can aid management scholars, practitioners, department heads, and university libraries to decide on efficient choices of journals for research and for manuscript submissions, for evaluation, and for subscriptions. Just seven management and social science journals, led by Strategic Management Journal, contain more than half of the cited articles published recently. Copyright © 1999 John Wiley & Sons, Ltd.